Upper ankle joint prostheses in haemophilia patients - Berdel, P.; Schott, D.; Pagenstert, G.; Pennekamp, P.; Oldenburg, J.; Wirtz, D. C.; Seuser, A.; Gravius, S. (Hämostaseologie, 2009)
Secondary arthrosis of the upper ankle joint (talocalcanean joint) is one of the most frequent forms of haemophilic arthropathy. It is a secondary form of arthrosis not only because of chronic synovitis and cartilage injury resulting from chronic recurrent intraarticular bleeds, but also due to the misalignment of the joint and abnormal joint stress. The consequences are manifest even in young patients and finally lead to subtalar joint ankylosis with the biomechanical disorder of foot drop (talipes equinus). In such clinical situations, implantation of a subtalar joint endoprosthesis is a viable alternative to arthrodesis. Case report:A man (age: 52 years), suffering from severe haemophilia A (residual FVIII activity < 1 %), no inhibitor formation. The patient has a history of several years of painful ankylosis of the right ankle joint and minor talipes equinus, and suffers from symptomatic talonavicular arthrosis. Open joint cleansing considerably improved mobility in the upper ankle joint and alleviated the pain in the talonavicular joint. However, the recovered mobility of the arthrotic upper ankle joint also activated the patient’s arthrosis, associated with severe pain. As there was no contraindication to upper ankle joint replacement, a cement-free prosthesis was implanted. Three months after surgery, the patient was mobile, with good foot rolling properties without orthopedic aids, and without pain in his upper joint ankle. Conclusion: In terms of biomechanics an upper ankle joint endoprosthesis is a superior alternative to arthrodesis in haemophilia patients. In order to minimize the complication rate, the treatment of haemophilia patients should be restricted to specially equipped interdisciplinary treatment centers with adequately trained and experienced surgeons as well as haemo -staseologists.
Keywords: Patients with haemophilia; total ankle arthoplasty